2012
DOI: 10.1561/100.00010098
|View full text |Cite
|
Sign up to set email alerts
|

Can Voter ID Laws Be Administered in a Race-Neutral Manner? Evidence from the City of Boston in 2008

Abstract: We use "race" as a shorthand for both race and ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…Furthermore, there is some research that finds that voter confidence can influence turnout (Alvarez, Hall, and Llewellyn 2008;Kerevel 2009), suggesting that pollworker discretion can have substantial consequences for voters. Second, previous research has suggested certain groups of voters may be disproportionately impacted by poll-worker discretion in the application of voter identification laws (Ansolabehere 2009;Cobb et al 2012;Page and Pitts 2009). If poll workers can use their discretion to discriminate against particular voters, as feared by Page and Pitts (2009), policy makers may wish to consider election reforms that restrict the ability of poll workers to use their own discretion in deciding what type of identification to accept from voters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, there is some research that finds that voter confidence can influence turnout (Alvarez, Hall, and Llewellyn 2008;Kerevel 2009), suggesting that pollworker discretion can have substantial consequences for voters. Second, previous research has suggested certain groups of voters may be disproportionately impacted by poll-worker discretion in the application of voter identification laws (Ansolabehere 2009;Cobb et al 2012;Page and Pitts 2009). If poll workers can use their discretion to discriminate against particular voters, as feared by Page and Pitts (2009), policy makers may wish to consider election reforms that restrict the ability of poll workers to use their own discretion in deciding what type of identification to accept from voters.…”
Section: Discussionmentioning
confidence: 99%
“…Recent voter studies in New Mexico in 2006 and 2008 found significant variation in the application of identification requirements; Hispanic, male, and Election Day voters were more likely to be asked for photo identification when none was required (Alvarez, Atkeson, and Hall 2013;Atkeson, Alvarez, and Hall 2010;). Other state and national studies showed minorities, both blacks and Hispanics, were more likely than whites to report showing identification (Ansolabehere 2009;Cobb et al 2012). In addition, an observational study in Los Angeles found that 29% of poll workers incorrectly indicated to observers that it was the law in California to show photo identification, and a significantly greater percentage of poll workers who worked in precincts with higher concentrations of minorities made such claims (Barreto, Cohen-Marks, and Woods 2009).…”
Section: Previous Research On Voter Identificationmentioning
confidence: 98%
See 2 more Smart Citations
“…We have identified only one other published study (Cobb et al 2012) similar to ours. It was carried out during the general election of 2008 in Boston to examine whether there were discrepancies by race and ethnicity in the proportion of voters asked to show ID at their polling place.…”
Section: Study Goalsmentioning
confidence: 57%